Data and computer communications - Stallings, William (bPrentice Hall, 2014)
Two-time winner of the best Computer Science and Engineering textbook of the year award from the Textbook and Academic Authors AssociationFor a one/two-semester courses in Computer Networks, Data Communications, and Communications Networks in CS, CIS, and Electrical Engineering departments